Catalytic Activity of Electroexplosive Cobalt Nanopowder in Hydrocarbon Synthesis by the Fischer–Tropsch Method; Catalysts; Vol. 16, iss. 1 - Popok E. V. Evgeniy Vladimirovich; Grushetsky E. V. Egor Vladimirovich; Morozova Ya. P. Yana Pavlovna; Bogdanov I. A. Ilya Aleksandrovich; Kirgina M. V. Mariya Vladimirovna; Mostovshchikov A. V. Andrey Vladimirovich (2026, 2026)
Title screen